A new insight in chimeric antigen receptor-engineered T cells for cancer immunotherapy - Erhao Zhang; Hanmei Xu (Journal of Hematology & Oncology, 2017)
Abstract Adoptive cell therapy using chimeric antigen receptor (CAR)-engineered T cells has emerged as a very promising approach to combating cancer. Despite its ability to eliminate tumors shown in some clinical trials, CAR-T cell therapy involves some significant safety challenges, such as cytokine release syndrome (CRS) and “on-target, off-tumor” toxicity, which is related to poor control of the dose, location, and timing of T cell activity. In the past few years, some strategies to avoid the side effects of CAR-T cell therapy have been reported, including suicide gene, inhibitory CAR, dual-antigen receptor, and the use of exogenous molecules as switches to control the CAR-T cell functions. Because of the advances of the CAR paradigm and other forms of cancer immunotherapy, the most effective means of defeating the cancer has become the integration therapy with the combinatorial control system of switchable dual-receptor CAR-T cell and immune checkpoint blockade.